1993
DOI: 10.1001/archsurg.1993.01420150055010
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole Thallium Imaging in Patients Being Considered for Vascular Procedures

Abstract: We routinely performed intravenous dipyridamole thallium imaging and resting radionuclide ventriculography on 190 patients being considered for elective vascular procedures. Patients with thallium redistribution underwent coronary arteriography. Patients in group 1 (n = 78) had clinical evidence of coronary artery disease, and patients in group 2 (n = 112) had no history or electrocardiographic evidence of coronary artery disease. The frequency of thallium redistribution was not significantly different in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Therefore, preoperative risk stratifi cation for possible cardiac events is very important, as well as the follow-up of postoperative patients. In the American College of Cardiology/American Heart Association (ACC/AHA) guidelines, noninvasive testing is useful for preoperative risk stratifi cation for high-risk surgical procedures [1], and many articles have discussed the usefulness of myocardial perfusion single photon emission computed tomography (SPECT) for preoperative risk stratifi cation of noncardiac surgery [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Most of these studies concluded that myocardial perfusion SPECT was predictive of perioperative cardiac events of noncardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, preoperative risk stratifi cation for possible cardiac events is very important, as well as the follow-up of postoperative patients. In the American College of Cardiology/American Heart Association (ACC/AHA) guidelines, noninvasive testing is useful for preoperative risk stratifi cation for high-risk surgical procedures [1], and many articles have discussed the usefulness of myocardial perfusion single photon emission computed tomography (SPECT) for preoperative risk stratifi cation of noncardiac surgery [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Most of these studies concluded that myocardial perfusion SPECT was predictive of perioperative cardiac events of noncardiac surgery.…”
Section: Introductionmentioning
confidence: 99%